Islamic events reminder system via short message service notifications alert - Maha Ibrahim Khaleel; Anwar Hamza Bresam (Institute of Advanced Engineering and Science, 2022)
For persons working in the field of modern technology, the lack of awareness about Islamic events remains a significant obstacle. One of the numerous reasons why the event gets forgotten on its designated date. This prompted the creation of an automatic reminder system with mobile technology integration. This paper has the purpose of assisting people in remembering their daily Islamic events, as well as serving as a model for informing people of Islamic occasions via short message service (SMS) notifications. As a result, the main goal is to develop an Islamic model that uses SMS to inform people. To develop a free system based on the concept of recalling the most significant events in Muslim history in order to keep people informed. (Microsoft Visual Studio.net and Microsoft SQL Server Management Studio Express) as our main database. The text message reminder system is made up of two parts: an SMS application for automatic text messaging and a web-based application for customer registration and automatic reminder scheduling. The automated method delivered 100% of the SMS messages to the participants throughout the pilot testing. Finally, the system displayed a notice indicating that the text messages were successfully despatched, and the application was confirmed to be functional.